Induction chemotherapy in locoregionally advanced nasopharyngeal carcinoma: A systematic review and meta-analysis - Wang, Bi-Cheng; Kuang, Bo-Hua; Liu, Xin-Xiu; Lin, Guo-He; Liu, Quentin (Frontiers in Oncology, 2022)
Background Adding induction chemotherapy to concurrent platinum-based chemoradiotherapy has significantly prolonged the survival time of patients with locoregionally advanced nasopharyngeal carcinoma. In this study, we intend to evaluate the survival outcomes, responses, and incidences of toxicities of induction chemotherapy and the differences between different strategies. Methods A comprehensive search was conducted in PubMed, Embase, Web of Science, and Cochrane CENTRAL on August 10, 2021. Single-arm or multi-arm prospective clinical trials on induction chemotherapy without targeted therapies or immune checkpoint inhibitors were included. Primary outcomes included survival outcomes, objective response rate, and disease control rate, and the secondary outcome was the rates of grade 3 or higher treatment-related adverse events. Results The 39 studies included in the systematic review and meta-analysis comprised 36 clinical trials and 5389 patients. The estimates for 3-year overall and fail-free survival rates were 87% and 77%. The estimates for 5-year rates of overall and fail-free survival were 81% and 73%. Gemcitabine plus platinum and docetaxel combined with 5-fluorouracil plus platinum strategies were associated with the highest rates of 3-year and 5-year overall survival. The objective response and disease control rates were 85% and 98% after the completion of induction chemotherapy. Neutropenia (27%) and nausea/vomiting (7%) were the most common grade 3 or higher treatment-related hematological and non-hematological adverse events during the induction phase. Conclusions Different induction chemotherapeutic strategies appear to have varying effects and risks; a comprehensive summary of the survival outcomes, responses, and toxicities in clinical trials may provide a crucial guide for clinicians.